Science and Polity in France : the Revolutionary and Napoleonic Years. - Gillispie, Charles Coulston (Princeton University Press, 2014)
From the 1770s through the 1820s the French scientific community predominated in the world to a degree that no other scientific establishment did in any period prior to the Second World War. In his classic Science and Polity in France: The End of the Old Regime, Charles Gillispie analyzed the cultural, political, and technical factors that encouraged scientific productivity on the eve of the Revolution. In the present monumental and elegantly written sequel to that work, which Princeton is reissuing concurrently, he examines how the revolutionary and Napoleonic context contributed to moderniz.